Revision total knee arthroplasty using a novel 3D printed titanium augment: A biomechanical cadaveric study. (October 2020) - Dion, C.; Yamomo, G.; Howard, J.; Teeter, M.; Willing, R.; Lanting, B.
Abstract: Background: During revision total knee arthroplasty (rTKA), proximal tibial bone loss is frequently encountered and can result in a less-stable bone-implant fixation. A 3D printed titanium revision augment that conforms to the irregular shape of the proximal tibia was recently developed. The purpose of this study was to evaluate the fixation stability of rTKA with this augment in comparison to conventional cemented rTKA. Methods: Primary total knee arthroplasty (pTKA) surgery was performed on 11 pairs of thawed fresh-frozen cadaveric tibias (22 tibias). Fixation stability testing was conducted using a three-stage eccentric loading protocol. Bone-implant micromotion was measured using a high-resolution optical system. The pTKA were removed. Revision TKA was performed using a 3D printed titanium augment or a standard fully cemented stem. The three-stage eccentric loading protocol was repeated and micromotion was measured for the revision implants. Results: After rTKA, the mean vertical micromotion was 28.1 μm ± (SD) 20.3 μm in the control group and 17.5 μm ± 18.7 μm in the experimental group. There was significantly less micromotion in the experimental group (p = 0.029). Conclusions: This study suggests that early fixation stability of revision TKA with the novel 3D printed titanium augment is better then the conventional fully cemented rTKA. The early press-fit fixation of the augment is likely sufficient for promoting bony ingrowth of the augment in vivo. Further studies are needed to investigate the long-term in-vivo fixation of the novel 3D printed augment. Graphical abstract: Image 1 Highlights: Revision total knee replacements: a novel 3D printed titanium implant for the tibia. Biomechanical cadaveric study of bone-implant micromotion under loaded conditions. Compared the 3D printed implant to the standard fully cemented tibial implant. The 3D printed titanium implant had better fixation-stability (less micromotion).